Effects of in vitro digestion and in vitro colonic fermentation on stability and functional properties of yerba mate (Ilex paraguariensis A. St. Hil.) beverages - Correa, Vanesa Gesser (2017)
The yerba mate or mate (YM) (Ilex paraguariensis A. St. Hil.) is a plant native from Paraguay, Uruguay, Argentina and Brazil. The powder of YM leaves and thin stems is used for the preparation of several stimulant drinks. The three most important are chimarrão (hot water extract of green dried leaves), tererê (cold water extract of green dried leaves) and mate tea (hot water extract of toasted leaves). Yerba mate is known to be rich in phenolic acids such as caffeic acid and chlorogenic acid and their derivatives and flavan-3-ols. Due this, their consumption has been considered beneficial for health and different bioactive properties have been related. It is well known that flavonoids and phenolic acids are extensively metabolized after ingestion and gastrointestinal absorption, being usually transformed into plasma metabolites with lower antioxidant activity than the precursor molecules. Studies mimetizing the digestion process have shown that the content of bioactive compounds is modified when passing through the various compartments of the gastrointestinal tract in consequence of pH alterations, enzymes action, and the metabolic activity of the intestinal microbiota. The aim of this work was to mimic the gastrointestinal digestion and the colonic fermentation of chimarrão, tererê and mate tea in order to get a possible estimate of the bioactive compounds from each preparation that effectively reach the circulation and the tissues. Raw and toasted yerba mate were obtained from reliable commercial sources in the South of Brazil. The beverages were prepared in the way they are popularly consumed. For the preparation of chimarrão and tererê, 1.5 L of water was added at 80 °C and 10ºC, respectively to 85 g of raw (green) yerba mate. After 5 min, the mixtures were filtered in a vacuum pump. For mate tea preparation, 1.5 L of water at 90 oC was added to 85 g of toasted yerba mate. After 5 min, the mixtures were also filtered in a vacuum pump. The three extracts were lyophilized and kept at -20 °C until analysis. In vitro gastrointestinal digestion was carried out simulating the oral, gastric and small intestine phases. For in vitro colonic fermentation a carbonate-phosphate buffer was used as the fermentation medium and the inoculum was prepared from fresh feces collected from male Wistar rats fed with standard diets and that had not received antibiotics at any time. The phenolic compounds were analyzed by LC-DAD-ESI/MSn (Dionex Ultimate 3000 UPLC, Thermo Scientific, San Jose, CA, USA). For the evaluation of antioxidant activity, six different methods were used: FRAP, ORAC, DPPH, ABTS, TBARS assay and inhibition of mitochondrial ROS production. To screen the antibacterial activity of the lyophilized extract seven Gram-negative bacteria and five Gram-positive bacteria were used. MIC determinations were performed by the microdilution method and the rapid p-iodonitrotetrazolium chloride (INT) colorimetric assay. MIC was defined as the lowest extract concentration that prevented changes in method and exhibited inhibition of bacterial growth. Sulforhodamine B assay was performed for cytotoxicity analysis. Four human tumor cell lines were tested: MCF-7 (breast adenocarcinoma), NCIH460 (non-small cell lung cancer), HeLa (cervical carcinoma) and HepG2 (hepatocellular carcinoma). For evaluation of the cytotoxicity in non-tumor cells, a cell culture (assigned as PLP2) was prepared from a freshly harvested porcine liver. The results were analyzed using one-way analysis of variance (ANOVA) followed by post hoc Student Newman Keuls testing. P values <0.05 were considered to be significant. The error parameters presented in tables are standard errors of the means. This treatment was carried out using the GraphPad Prism software (version 5.0). Chimarrão presented the highest level of total phenolic compounds and flavonoids (111.46 ± 3.85 mg/g extract and 5.61±0.06 mg/g extract, respectively), followed by tererê (69.01 ± 4.72 and 1.00 ± 0.01 mg/g extract, respectively), and mate tea (64.35 ± 0.73 and 0.02 ± 0.01 mg/g extract, respectively). The lowest amount of phenolic compounds in mate tea can be explained by the possible degradation of some compounds by the high temperatures applied in the toasting process. After in vitro digestion total phenolic compounds of chimarrão, tererê and mate tea decreased by 74.69±5.48, 69.01±4.72 and 51.60±1.89 mg/g extract, respectively, representing reductions of 33%, 24% and 20%, respectively. This behaviour indicates that the transformation of the phenolic compounds may be influenced by pH changes and by interactions with other constituents during in vitro digestion. After colonic fermentation, no significant alterations in the total phenolic compounds were observed in chimarrão and tererê, while in mate tea, total phenolic compounds decreased by 34.64± 0.20 mg/g extract, what represents a reduction of 33%. In general, the in vitro gastrointestinal and colonic fermentation caused a reduction, to a greater or lesser degree, in the antioxidant capabilities of the yerba mate beverages, except in the ABTS assay. Although the decreases in the antioxidant activities were statistically significant (p≤0.05) in several cases, the extracts maintained antioxidant properties. The green and toasted yerba mate extracts exhibited antibacterial activity against all Gram positive and Gram negative bacteria tested. Also, all yerba mate extracts were more active against Gram positive bacteria, especially Staphylococcus aureus, MRSA-methicillin-resistant Staphylococcus aureus, and MSSA-methicillin-susceptible Staphylococcus aureus. In general, the in vitro digestion and colonic fermentation barely affected the antimicrobial activities of the extracts. However, after in vitro digestion and colonic fermentation, the extracts were more active against S. aureus, MRSA and MSSA. The crude extracts showed cytotoxicity against HeLa cells. This cytotoxicity was slightly affected by in vitro digestion and colonic fermentation. Interestingly, the colonic fermentation improved the cytotoxicity of the mate tea extract against all tumor cell lines, except HepG2. None of the tested extracts showed toxicity against normal (non-tumor) porcine liver primary cells (GI50>400 μg/mL). The results of this study demonstrate, for the first time, the effects of both in vitro digestion and in vitro colonic fermentation of yerba mate prepared in the three most common forms of consumption (chimarrão, tererê and mate tea). Despite the decrease in the phytochemicals content, yerba mate beverages maintained their functional properties such as antioxidant, antibacterial and antitumor activities after in vitro gastrointestinal digestion and in vitro colonic fermentation.